2011
DOI: 10.4161/epi.6.1.13392
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative, high-resolution epigenetic profiling of CpG loci identifies associations with cord blood plasma homocysteine and birth weight in humans

Abstract: Supplementation with folic acid during pregnancy is known to reduce the risk of neural tube defects and low birth weight. It is thought that folate and other one-carbon intermediates might secure these clinical effects via DNA methylation. We examined the effects of folate on the human methylome using quantitative interrogation of 27,578 CpG loci associated with 14,496 genes at single-nucleotide resolution across 12 fetal cord blood samples. Consistent with previous studies, the majority of CpG dinucleotides l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(145 citation statements)
references
References 39 publications
(80 reference statements)
5
136
3
1
Order By: Relevance
“…This does not rule out the possibility that a minority of genes are influenced by a common environment. Indeed, previous genome-scale studies of DNA methylation have found a range of probes significantly associated with maternal environmental, from 0.6% (Breton et al 2009) and 1.1% (Fryer et al 2011) to 23% (Katari et al 2009). Because the accuracy of the estimation of effect size depends on study power, further investigation in larger numbers of twins is needed (Visscher 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This does not rule out the possibility that a minority of genes are influenced by a common environment. Indeed, previous genome-scale studies of DNA methylation have found a range of probes significantly associated with maternal environmental, from 0.6% (Breton et al 2009) and 1.1% (Fryer et al 2011) to 23% (Katari et al 2009). Because the accuracy of the estimation of effect size depends on study power, further investigation in larger numbers of twins is needed (Visscher 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The relative ease of use and ability to analyse multiple samples in parallel has resulted in a recent increase in reports using these arrays on a variety of research areas (e.g. Banister et al 2011, Cotton et al 2011, Fackler et al 2011, Fryer et al 2011, Martino et al 2011. Although these arrays, post-sodium bisulphite conversion, report on methylation, it is important to bear in mind that they examine a discrete number of CpGs within a region and not methylation of multiple, contiguous CpGs within, for example, a CpG island.…”
Section: Chips With Everythingmentioning
confidence: 99%
“…However, no attempts were made to correlate methylation with gene expression. Other gestational CVD risk factors shown to influence DNA methylation in humans include maternal smoking (60), folate intake (61), and levels of homocysteine (62), which is involved in the development of atherosclerosis by inducing changes in DNA methylation in multiple genes in vascular smooth muscle cells and is the biomarker most directly implicated in epigenetic mechanisms relating to CVD risk (2). Epigenetic marks at these genes are sensitive to the prenatal environment (63).…”
Section: Epigenetics and Its Role In Developmental Programming Of Cvdmentioning
confidence: 99%